An endemic neurological disorder in tribal Australian aborigines. Issue 8 (August 1980) - Kiloh, L G; Lethlean, A K; Morgan, G; Cawte, J E; Harris, M
Abstract : Thirteen, and possibly sixteen cases of neurological disorder have been identified in a population of approximately 1100 tribal aborigines living in Groote Eylandt and the adjacent mainland. There were two relatively distinct clinical pictures: one coming on in childhood involved the motor system, the patients often having remarkably lax ligaments; and the other, generally of later onset, comprising cerebellar, upper motor neurone and sometimes supranuclear ophthalmoplegic features. There was some evidence that the two syndromes are varieties of a single condition. No causal factors were identified but there were indications that the disorder might be genetically determined. Attention is drawn to the similarities between this disorder and other ethnic-geographic isolates, particularly the ALS-Parkinsonism-dementia complex of Guam.